2015
DOI: 10.1016/j.marpolbul.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from TBT pollution in English Channel environments: A problem solved?

Abstract: Following recognition of effects in the 1980s, tributyltin (TBT) has been monitored at sites in the English Channel to evaluate the prognosis for biota -spanning the introduction of restrictions on TBT use on small boats and the recent phase-out on the global fleet. We describe how persistence and impact of TBT in clams Scrobicularia plana has changed during this period in Southampton Water and Poole Harbour. TBT contamination (and loss) in water, sediment and clams reflects the abundance and type of vessel ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…A full analysis (see Table S2) of the mesocosm sediment (based on UK Accreditation Servicemethodology, ISO/IEC 17025:2005) confirms a poorly sorted sediment with high levels of silt/clay (55% < 63 µm; Md =48 µm) and low levels of metal and organic pollution except for TBT (tributyltin as cation) which exceeded the SQG (Simpson et al, 2013) and was higher than similar areas with greater perceived impacts (Langston et al, 2005). For copper and zinc, both the UK Accreditation Service aqua regia (Table S2) extraction and the BCR extraction of the control treatment at time 0 (Cu: 8 mg kg -1 ; zinc: 23 mg kg -1 , Table 1) confirm that the background concentrations of copper and zinc were low and compared to other marine sites (Bryan and Langston, 1992;McQuillan et al, 2014) the sediment has very low contamination.…”
Section: Metal Bioavailabilitymentioning
confidence: 90%
“…A full analysis (see Table S2) of the mesocosm sediment (based on UK Accreditation Servicemethodology, ISO/IEC 17025:2005) confirms a poorly sorted sediment with high levels of silt/clay (55% < 63 µm; Md =48 µm) and low levels of metal and organic pollution except for TBT (tributyltin as cation) which exceeded the SQG (Simpson et al, 2013) and was higher than similar areas with greater perceived impacts (Langston et al, 2005). For copper and zinc, both the UK Accreditation Service aqua regia (Table S2) extraction and the BCR extraction of the control treatment at time 0 (Cu: 8 mg kg -1 ; zinc: 23 mg kg -1 , Table 1) confirm that the background concentrations of copper and zinc were low and compared to other marine sites (Bryan and Langston, 1992;McQuillan et al, 2014) the sediment has very low contamination.…”
Section: Metal Bioavailabilitymentioning
confidence: 90%
“…The X and Y axes represent the longitude Northern length (NL) and the latitude Eastern length (EL), respectively. Langston et al, 2015;Nicolaus and Barry, 2015;Wilson et al, 2015;HELCOM, 2018;Schøyen et al, 2018). The unequal recovery in time is not surprising since the 1989 TBT restrictions on small ships had mainly a local impact in predominantly recreational and small ships areas.…”
Section: Tbt Levels In the Southern North Seamentioning
confidence: 99%
“…This paper assesses different aspects of TBT pollution in C. crangon in its main distribution range, the southern North Sea and does not focus on an overall review on TBT data and effects in the marine environment, as the TBT levels vary by a high factor in different locations. For comprehensive reviews, we refer to, among other (Evans et al, 1996;Fent, 1996;Champ, 2000;Birchenough et al, 2002;Stronckhorst and van Hattum, 2003;Antizar-Ladislao, 2008;Morton, 2009;Oliveira et al, 2009;Rodríguez et al, 2009;Sousa et al, 2009;Bengtsson and Wernersson, 2012;Sunday et al, 2012;Matthiessen, 2013;Wetzel et al, 2013;OSPAR, 2014;Langston et al, 2015;Nicolaus and Barry, 2015;Wilson et al, 2015;Schøyen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Organotin compounds have teratogenic properties and can cause disruptions to the reproductive function in mammals, as well as acting as endocrine disruptors, hepatoxins, immunotoxins, neurotoxins and obeseogens [5][6][7]. Recent studies have shown a significant reduction in pollution by TBT along coastlines, as well as the biological recovery of many marine species [8]. Despite the observed improvements from reduced concentrations of organotin compounds; sediment legacy of TBT is still associated with shipping facilities, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…ports, docks and maintenance facilities, offshore shipping routes and anchorages. The half-life of TBT within aquatic compartments is somewhat ambiguous and is largely dependent on the composition of the surrounding water and the associated benthic deposits (with anoxic marine sediment demonstrating greatest half-lives of >10 years) [8]. Organotins are lipid soluble and adsorb easily into the fatty tissues of marine biota.…”
Section: Introductionmentioning
confidence: 99%